An introduction to pidgins and creoles - Holm, John A. (Cambridge textbooks in linguistics., 2000)
"This textbook is a clear and concise introduction to the study of how new languages come into being." "Starting with an overview of the field's basic concepts, it surveys the new languages that developed as a result of the European expansion to the Americas, Africa, Asia and the Pacific. Long misunderstood as 'bad' versions of European languages, today such varieties as Jamaican Creole English, Haitian Creole French and New Guinea Pidgin are recognized as distinct languages in their own right.".